Criteria of geotourism valorization specified for various recipients // Kryteria waloryzacji geoturystycznej na potrzeby różnego rodzaju odbiorców - Doktor, Marek; Miśkiewicz, Krzysztof; Welc, Ewa M.; Mayer, Wojciech (Geotourism/Geoturystyka, 2017)
The following paper presents methodology of valorization of geotourism objects adapted to meet the expectations and needs of various groups of potential recipients: tourists (casual, witting, hobbyist), educators (school teachers, academic staff, guides, organizers) and investors (owners, managers). Any geotourism object can be valorized using four principal categories of criteria: visual, cognitive, functional and investing. Each category is evaluated separately and selection of particular criteria depends on the needs of given recipient. // W artykule zaproponowano sposób waloryzacji obiektów geoturystycznych uwzględniający potrzeby potencjalnych odbiorców: turystów (przypadkowy, świadomy, pasjonat), edukatorów (nauczyciel szkolny i akademicki, przewodnik, organizator turystyki specjalistycznej), inwestorów (właściciel, zarządca). Na ocenę obiektu składają się cztery główne kryteria: wartość wizualna, wartość poznawcza, wartość użytkowa oraz warunki i potrzeby inwestycyjne. Każde z kryteriów oceniane jest osobno, a o ważności i doborze kryterium decyduje samodzielnie odbiorca waloryzacji.